1998
DOI: 10.1093/oxfordjournals.pcp.a029388
|View full text |Cite
|
Sign up to set email alerts
|

The Maize Glutamine Synthetase GS1- Gene is Preferentially Expressed in Kernel Pedicels and is Developmentally-Regulated

Abstract: The pedicel region of Zea mays kernels contains a unique form of maize glutamine synthetase (GS), GS pl . RNA blot analysis using GS gene-specific probes revealed that the expression of the GS,. 2 gene was specific to the pedicel and that it increased in the kernels during development. This pattern of the maize GS,. 2 gene expression is consistent with the tissue specificity of the GS pl protein and suggests that it encodes the GS pl isoform of maize GS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…OsGS1;3 was expressed mainly in spikelets. Similar results were obtained in maize in which one of the five GS1 genes is also preferentially expressed in kernel pedicels (Rastogi et al. , 1998).…”
Section: Discussionsupporting
confidence: 82%
“…OsGS1;3 was expressed mainly in spikelets. Similar results were obtained in maize in which one of the five GS1 genes is also preferentially expressed in kernel pedicels (Rastogi et al. , 1998).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, this finding reinforces the current consensus that each individual GS gene product in a given plant species may play a specific role during plant growth and development (Cren and Hirel, 1999). In maize, it has been previously shown that the five members of the cytosolic GS multigene family may be differentially expressed in different organs including roots and leaves (Sakakibara et al, 1992b;Li et al, 1993) and developing seeds (Rastogi et al, 1998). It has also been demonstrated that, at least in vegetative organs, the source of N may be an additional factor that may modulate their transcription (Sakakibara et al, 1992a).…”
Section: Genetic Analysis Of N Metabolism In Relation To Maize Kernelmentioning
confidence: 99%
“…Although this has never been fully demonstrated, it has been proposed by several authors that each cytosolic GS isoenzyme plays a specific physiological role suited to the physiological need of the plant (Woodall et al, 1996;Cren and Hirel, 1999). This may explain why seed-specific GS1 isoenzymes are differentially expressed during certain phases of seed development (Rastogi et al, 1998).…”
mentioning
confidence: 99%
“…The GS 1‐2 gene encodes an isozyme of glutamine synthetase that is strongly expressed in the pedicel of developing maize seeds (Rastogi et al 1998) and whose promoter is capable of driving gene expression exclusively in the maternal tissues of developing seeds of transgenic maize plants (Muhitch et al 2002). Here, the effects of truncation from the 5′ end of the upstream region of the promoter were examined on transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The GS 1-2 gene encodes an isozyme of glutamine synthetase that is strongly expressed in the pedicel of developing maize seeds (Rastogi et al 1998) and whose promoter is Table 1. Efficiency of transformation of maize with GS 1-2 /GUS heterologous gene promoter deletion series.…”
Section: Discussionmentioning
confidence: 99%